The effect of yoga movements in reducing complaints symphysis pubis dysfunction in pregnancy - Ratih Kumorojati; Alfie Ardiana Sari; Ika Fitri Ayuningtyas (Alma Ata University Press, 2023)
Background: The incidence of Section Caesarea (SC) based on the results of the 2018, states that the highest prevalence is in the DKI Jakarta area with a percentage reached 31.3% while the Papua region percentage is only 6.7%. It is known that the causes of birth with CS include, a narrow pelvis, disproportion of the fetal head, malposition of the fetus, and disorders of the descent of the fetal head which often cause complaints of symphysis pubis dysfunction (SPD). Every pregnant woman needs to empower herself to increase her self-confidence in facing the pregnancy process until before delivery. Several studies have stated that practicing yoga during pregnancy can reduce pregnancy complaints. During the Covid-19 pandemic, pregnant women were limited to doing activities outside the home. In this case, independent yoga media is needed that is safe, easy to understand, and as a guide for pregnant women, both in the form of videos, flashcards, spin cards, and picture cards of practical yoga movements.Objectives: To find out the effectiveness of yoga movements in dealing with complaints of symphysis pubis dysfunction in pregnancy.Methods: This research method uses quasi-experimental research with a one-group pre-test design which reveals a causal relationship involving one group of subjects. Respondents consisted of 25 pregnant women entering the third trimester of pregnancy with the inclusion criteria of pregnant women experiencing dysfunction of the symphysis pubis before the intervention. The interventions that will be carried out are measuring pain scales, printing yoga movement cards, teaching, and doing yoga 4 times in 1 month.Results: It is known that the number of respondents who did yoga before the intervention was mostly in the mild pain category (36%) and moderate (28%). After the intervention, the majority of respondents were in the no-pain category (44%). Respondents with severe pain before intervention (16%) decreased to (8%) post-intervention. The results of statistical tests using the Wilcoxon test obtained p = 0.036 where this value is below 0.05, which means that there is an effect of yoga movements in reducing complaints of symphysis pubis dysfunction in pregnancy.Conclusions: From the results of the research that has been done, it can be concluded that there is an influence of yoga movements in reducing complaints of symphysis pubis dysfunction in pregnancy. There were significant changes in pregnant women before and after the intervention. Therefore pregnant women are encouraged to do yoga regularly to reduce complaints of pregnancy discomfort which can interfere with the delivery process.